2016
DOI: 10.1177/1098612x16666119
|View full text |Cite
|
Sign up to set email alerts
|

Does categorisation of lymphoma subtypes according to the World Health Organization classification predict clinical outcome in cats?

Abstract: Objectives The purpose of this study was to specify lymphoma subtypes according to the World Health Organization (WHO) classification in a group of cats and to investigate their potential prognostic value. Methods Records of cats from the University of Veterinary Medicine Vienna suffering from lymphoma were reviewed in this retrospective study. To diagnose various subtypes specified in the WHO classification, histopathological and immunohistochemical examinations, as well as clonality assays in some cases, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 51 publications
3
18
0
1
Order By: Relevance
“…Indeed, 12 cats underwent surgical debulking, followed by subsequent chemotherapy in 9 of them, with no significant improvement of outcome. It may be possible that tumor resection does not benefit cats with LGL lymphoma due to its peculiar biology, as previously described, or the small number of cats may have rendered the results statistically not significant.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Indeed, 12 cats underwent surgical debulking, followed by subsequent chemotherapy in 9 of them, with no significant improvement of outcome. It may be possible that tumor resection does not benefit cats with LGL lymphoma due to its peculiar biology, as previously described, or the small number of cats may have rendered the results statistically not significant.…”
Section: Discussionsupporting
confidence: 69%
“…Due to the poor outcome and the presence of severe clinical signs, euthanasia is usually carried out soon after diagnosis . Nevertheless, treated individual cases are occasionally described as harboring a more favorable prognosis …”
Section: Introductionmentioning
confidence: 99%
“…Several subtypes of AL can be defined according to the histological grade (low, intermediate or high), cell size (small or large) and phenotype (T or B) of the neoplastic lymphocytes [ 6 , 8 , 14 , 18 , 20 – 23 ]. Originally, lymphomas were classified according to the World Health Organization (WHO) scheme into Enteropathy-Associated T-cell Lymphoma (EATL) type 1 and 2.…”
Section: Introductionmentioning
confidence: 99%
“…Sato et al [37] showed a shorter survival time in alimentary (48 days) lymphomas than in cats with nasal (135 days) or mediastinal (143 days) lymphomas. Wolfesberger et al [38] reported the highest survival time in intestinal T-cell lymphomas (1.7 years) compared to large B-cell lymphoma (4.5 months) or peripheral T-cell lymphoma (6.1 months). In our study, seven out of 12 cats with lymphomas were either euthanized or died during or shortly after surgery.…”
Section: Discussionmentioning
confidence: 99%